Technics for Measuring Plantar Pressure Distribution during Gait - Christoforidis Χρήστος; Aggeloussis Νίκος; Kampas Αντώνης (Inquiries in Physical Education and Sport, 2007)
Distribution of the pressure that is exerted at the soles of the feet is a useful clinical tool for the diagnosis of orthopedical, neurological and myoskeletal abnormalities. The present study records the various systems that are being used for the measurement of the plantar pressure, and reports the research methodologies and the techniques that are applied to assess the pressure that appears at the soles of the feet during gait. In specific, it includes reference to the various measurement protocols used for the assessment of foot pressure, the equipment, and the techniques that are applied for collecting and analyzing the data. Moreover, it defines the parameters of plantar pressure that are to be taken into consideration when trying to reach conclusions about the functional ability of the lower limbs.